Cytological Pattern of Salivary Gland Lesions - Abdul Rauf ,Ammara Ejaz, Abdul Rauf ,Ammara Ejaz (Journal of Rawalpindi Medical College, 2017)
To study the cytological pattern of salivary glands swellings on fine needle aspiration cytology (FNAC). Methods: Patients who underwent fine needle aspiration cytology (FNAC) for their salivary gland swellings, were included. Data was analyzed from various angles including site, diagnostic categories, diagnostic entities, age and gender. Results: Parotid gland (74.3%) was the most frequently affected site, followed by submandibular gland (23.6%). The cases were divided into four main reporting groups i.e. unsatisfactory, inconclusive/ lesion of undetermined significance, non neoplastic and neoplastic constituting 0.7%, 3.6%, 22.9% and 72.9% of all the lesions respectively. Non neoplastic lesions included non specific sialadenitis, cystic lesions without any evidence of neoplasia and sialadenosis comprising 43.8%, 37.5% and 18.8% of these lesions respectively. Neoplastic lesions were divided into three categories namely benign, malignant and indeterminate. Benign tumors constituted 79 (56.4%), malignant neoplasms consisted of 8 (5.7%) and indeterminate category contained 15 (10.7%) of all cases. Mean age was 43 years and MF ratio was 1:1.7. Pleomorphic adenoma was the most frequent diagnosis among all cases, in all neoplasms as well as in benign neoplasms. Conclusion: Parotid was the commonest site of involvement. Pleomorphic adenoma and mucoepidermoid carcinoma were the most common lesions in benign and malignant neoplastic categories respectively.